THE EFFECT OF ADMINISTRATION OF COMBINATION OF OVAPRIME HORMONES WITH OXYSTOSIN TO OVULATION AND PRESSING OF SELF-FISHED EGG (Ompok rhadinurus) - Saputra, Muhammad Rizki; Nuraini, Nuraini; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in May to June 2018 at the Fish Seed Hall Laboratory (BBI) headland of the Fisheries and Marine Service, Rokan District, downstream. The purpose of this study was to determine the efficacy of ovulation and hatching of fish eggs (Ompok Rhadinurus) which were injected with a combination of the hormone ovaprim with oxytocin at different doses. The method used in this study is the experimental method that uses one-factor Completely Randomized Design (CRD) consisting of five treatments with three replications. The treatments applied in this study are: P1: Injection with 25% ovaprim + 75% oxytocin, P2: Injecting with 50% ovaprim + 50% oxytocin, P3: Injecting with 75% ovaprim + 25% oxytocin, P4: Injection with 100% ovaprim, P5: Injecting with 100% oxytocin. The results showed that the best treatment for the effect of ovulation and anchovy egg maturation (Ompok Rhadinurus) was P2: 50% ovaprim + 50% oxytocin which resulted in a latency time of 7 hours 38 minutes, the number of eggs stripping as many as 214 grains / g parent, value ovisomatic index of 16.14%, increase in egg diameter of 0.30 mm, fertilization value of 73.13%, hatching value of 82%, and survival value (SR5 days) of 58.31%. Water quality parameters are: temperature 24-28 ?c, pH: 5-6, DO: 5.2 - 6.3 mg / L. Keywords: Injections, Oxytocin Hormones, Ovaprim Hormones, Stem Fish (Ompok      rhadinurus)